(untitled) (Mongolian Journal of Agricultural Sciences, 2015)
The human antimicrobial peptide, LL-37 gene was overexpressed in Chinese cabbage ‘Osome’ (Brassica rapa) by Agrobacterium tumefaciens-mediated transformation. In order to increase the expression of the antimicrobial peptide, we used RolA intron sequence in front of the LL-37peptide gene. We confirmed the expression of LL-37 in cabbage by RT-PCR and Western Blot analysis. Four transgenic T1 plants were confirmed that LL-37 was expressed. Cabbages expressing the humanLL-37 gene were challenged by various plant pathogen. Transgenic cabbage plants overproducing human LL-37 are expected to possess a durable and wide-spectrum resistance against various pathogens. Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 124-130